Ternary Hybrid Pvdf-Hfp Pani Go Polymer Electrolyte Membrane For Lithium Ion Battery - Farooqui, Usaid Ur Rehman (2019)
Poly(vinylidene fluoride-co-hexafluoropropylene) PVDF-HFP is a promising candidate as a separator in lithium-ion batteries owing to its outstanding chemical resistance, high mechanical and thermal stability with lower cost; however, its pristine form has limited characteristics that require further modification to achieve enhanced performance. Therefore, in this research ternary hybrid PVDF-HFP/PANI/GO were develop and the scope were divided into three phase which at first, different dosages of polyaniline (PANI) (1 wt%, 2 wt%, and 3 wt%) are incorporated into PVDF-HFP polymer matrix to fabricate PVDF-HFP/PANI polymer electrolyte membrane by using breath-figure method. The PANI (2 wt%) inclusion influenced the ionic conductivity and enhanced it from 1.98 × 10-4 S cm-1 of pristine PVDF-HFP membrane to 1.04 × 10-3 S cm-1; however, its plasticizing effect resulted in tensile strength of pristine PVDF-HFP membrane from 4.2 MPa to 2.8 MPa. Secondly, the effect of graphene oxide (GO) is investigated by varying different amount of GO (1 wt%, 2.5 wt%, and 5 wt%) into PVDF-HFP polymer matrix. The GO (2.5 wt%) addition remarkably enhanced the tensile strength of PVDF-HFP membrane from 4.2 MPa to 12.5 MPa; however, it showed negligible effect on ionic conductivity of pristine PEM. Therefore, in third phase, PANI/GO composite material is combined for the unique properties of both the fillers. The ternary hybrid PVDFHFP/ PANI (2 wt%)/GO (10 wt%, 25 wt%, and 40 wt%) PEMs are synthesized and characterized for lithium ion batteries. The obtained PVDF-HFP/PANI/GO ternary membrane showed a remarkable improvement in tensile strength up to 8.8 MPa. Furthermore, the PVDFHFP/ PANI/GO ternary membrane exhibited outstanding thermal stability with Td up to 498°C, improved morphology, highest electrolyte uptake (367.5%) and an excellent porosity of around 89%. Moreover, the obtained optimum pristine PVDF-HFP, PVDFHFP/ PANI, and PVDF-HFP/PANI/GO PEMs were considered for further electrochemical characterization and modelling. Also, the R-CPE model provided a best quality fit with MSE value of around 5% compared to R-C and R-L model. Further, the prepared optimum PEMs is successfully applied in lithium ion battery and showed good specific capacity for initial 10 cycles. However, PVDF-HFP/PANI/GO ternary PEM resulted in better stability compared to other PEMs; therefore, it is tested for capacity retention and it retained over 95% capacity after 30 cycles. In conclusion, the proposed PVDF-HFP/PANI/GO ternary membrane is a potential candidate as a separator in future lithium-ion batteries.